A phase 2a double-blind, placebo-controlled, randomized clinical trial evaluating the efficacy and safety of NuGel, a novel topical GPCR19-mediated inflammasome inhibitor, in patients with mild to moderate atopic dermatitis: a proof-of-concept study with Post-hoc biomarker analysis - Baek, Gyeong Ho; Kim, Bo Ri; Shin, Jung-Won; Huh, Chang Hun; Hwang, Jungjoong; Ko, Sungmin; Kim, Siwon; Ho, Pil-Su; Kim, Kyu-Han; Park, Chun Wook; Seo, Seong Jun; Park, Chang-Ook; et al. (Frontiers in Immunology, 2025)
BackgroundCurrent guidelines to treat atopic dermatitis (AD) overlook disease heterogeneity, limiting personalized care. This study assessed NuGel, a topical GPCR19 agonist, for efficacy, safety, and predictive baseline biomarkers in AD patients.MethodsIn a multicenter, double-blind, randomized, placebo-controlled Phase 2a trial (August 2020–September 2021, five hospitals, 80 participants), patients received placebo, 0.3% NuGel, or 0.5% NuGel twice daily for four weeks.ResultsNuGel (0.3% [Nu0.3] and 0.5% [Nu0.5]) was well-tolerated, with no adverse drug reactions or serious adverse events. Nu0.3 showed a significant decrease in EASI score from baseline (-12.2%, [-30.3%, 5.9%], p = 0.04). Treatment with Nu0.5 resulted in a numerically decreased EASI score (-11.9%, [-34.9%, 11.1%], p > 0.05), which is comparable with placebo group (-2.9%, [-21.5%, 15.6%], p > 0.05). No significant difference was observed between groups (p>0.05). Plasma proteomic analysis identified biomarkers associated with blood coagulation, complement activation, and cell adhesion as predictors of response to Nu0.5. Patients with baseline profiles characterized by K2C5high, ENTP6low, or CRKlow demonstrated significant clinical improvement when treated with Nu0.5 compared to the placebo group. Among these, the CRKlow subgroup, comprising 54.3% of the biomarker analysis set, showed a ΔEASI of -61.3% [-99.9, -22.8; p = 0.003] and a ΔIGA of -35.2% [-58.2, -12.1; p = 0.004] compared to the placebo group. The biomarker signature demonstrated high predictive accuracy (AUC = 0.92, p = 0.002). Logistic regression analysis revealed that the threshold of predicted probability derived from the baseline plasma level of K2C5 and ENTP6 successfully stratified 100% of participants who responded to Nu0.5 (ΔEASI from baseline ≤ -50%), whereas none (0%) in the placebo group responded (p = 0.035).ConclusionBaseline biomarkers, such as K2C5, ENTP6, and CRK, may serve as predictors of clinical improvement in AD patients treated with Nu0.5, highlighting the potential for personalized treatment strategies. Further research is required to validate these findings in larger patient cohorts.Clinical trial registrationhttps://clinicaltrials.gov/, identifier NCT04530643.